2022
DOI: 10.18196/jrc.v3i5.15661
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multi-Robotic Arm System for Sorting System Using Computer Vision

Abstract: This paper develops a multi-robotic arm system and a stereo vision system to sort objects in the right position according to size and shape attributes. The robotic arm system consists of one master and three slave robots associated with three conveyor belts. Each robotic arm is controlled by a robot controller based on a microcontroller. A master controller is used for the vision system and communicating with slave robotic arms using the Modbus RTU protocol through an RS485 serial interface. The stereo vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…In [22], a system was proposed with multiple robot arms and special cameras to correctly organize objects based on their size and shape. In [23], a system was introduced that used cameras to detect fires and smoke indoors. Many studies suggested different models for proximity detection in different scenarios.…”
Section: Wwwetasrcom Sajini and Pushpa: Sensor Enabled Proximity Dete...mentioning
confidence: 99%
“…In [22], a system was proposed with multiple robot arms and special cameras to correctly organize objects based on their size and shape. In [23], a system was introduced that used cameras to detect fires and smoke indoors. Many studies suggested different models for proximity detection in different scenarios.…”
Section: Wwwetasrcom Sajini and Pushpa: Sensor Enabled Proximity Dete...mentioning
confidence: 99%
“…Due to their versatility, ResNets are popular across numerous fields and have multiple implementations, such as ResNet-18 [78], [79], ResNet-34 [80], ResNet-50 [81], and ResNet-101 [82]. The integration of these technologies can also extend to the development of multi-robotic arm systems [32] and mobile robots capable of facial detection [33]. This combination has led to the creation of increasingly accurate systems while streamlining the design process through the use of various tools and functions.…”
Section: Introductionmentioning
confidence: 99%